2020
DOI: 10.3389/fcell.2020.00826
|View full text |Cite
|
Sign up to set email alerts
|

Metabonomic Profile of Macrosteatotic Allografts for Orthotopic Liver Transplantation in Patients With Initial Poor Function: Mechanistic Investigation and Prognostic Prediction

Abstract: Background Our previous study revealled amplified hazardous effects of macrosteatosis (MaS) on graft failure (GF) in recipients with severe liver damage in short post-operative days, with vague mechanism inside. Aim We aimed to uncover the molecular mechanism of donor MaS on GF, and construct the predictive model to monitor post-transplant prognosis based on “omics” perspective. Methods Ultra-performance liquid chromatography coupled to mass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 59 publications
1
14
0
Order By: Relevance
“…As presented in Tables 1 and 2, a total of eight studies have reported the connections between omics data and phenotypes in clinical LT. 31,[37][38][39][42][43][44][45] Metabolomics is the most-used assay involved in all omics studies. Most researchers prefer to collect samples from graft tissues and omics data from recipient sera, but such were only assayed in three studies.…”
Section: Current Application Of Omics Data In Clinical Lt Investigationsmentioning
confidence: 99%
See 3 more Smart Citations
“…As presented in Tables 1 and 2, a total of eight studies have reported the connections between omics data and phenotypes in clinical LT. 31,[37][38][39][42][43][44][45] Metabolomics is the most-used assay involved in all omics studies. Most researchers prefer to collect samples from graft tissues and omics data from recipient sera, but such were only assayed in three studies.…”
Section: Current Application Of Omics Data In Clinical Lt Investigationsmentioning
confidence: 99%
“…It is noteworthy that dysfunctional glycerophospholipid metabolism was also shown to be a major cause of macrosteatosis (MaS) and graft failure (GF) in a prior study from our center. 39 We speculated that a derangement in glycerophospholipid might be a link to inferior organ quality, such as MaS, to early graft dysfunction and final organ failure in LT.…”
Section: Omics Data For Assessing Organ Function After Ltmentioning
confidence: 99%
See 2 more Smart Citations
“…The metabolome represents the downstream products of the genome and proteome, finally resulting in a specific omics composition ( Yan et al, 2018 ; Rinschen et al, 2019 ). It has commonly been used as an approach to identify biomarkers in the diagnosis and prediction of disease ( Li et al, 2019 ; Rinschen et al, 2019 ; Zhou et al, 2019 ; Abooshahab et al, 2020 ; Jiang et al, 2020 ; Liu Z. et al, 2020 ; Souto-Carneiro et al, 2020 ). In view of the unique characteristics of urine, an increasing number of studies have used urinary metabolomics for biomarker discovery in recent years ( Kwon et al, 2020 ; Liu W. et al, 2020 ; Olesova et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%